Analysis of Marketing System for Sweet Orange in Darchula District, Nepal - Joshi, Naresh; Bhatta, Kiran Prasad (Journal of Agriculture and Resource Management, 2024)
Sweet orange is one of the major fruits grown in the mid-hills of Nepal. It ranks second among the citrus fruits in terms of area and production but farmers have yet to receive potential benefit from this enterprise, mostly due to market issues. This study analyzed different aspects of sweet orange marketing to support overcome these problems. The research was conducted in the two Palikas (Mahakali municipality and Lekam rural municipality) of Darchula district. Altogether 50 samples each were selected randomly from these two Palikas, totaling 100 samples. The collected data were processed and analyzed using MS Excel and STATA. Sweet orange was found to be highly profitable enterprises with high Benefit-Cost (BC) ratio but marketing is crucial for this. Four major marketing channels from producers to (i) Consumers; (ii) Retailers; (iii) Wholesalers and; (iv) Preharvest Contractors were observed. Among these, Producers-Consumers was the most common as well as profitable, Looking at the marketing margin (Rs. 6.81) and Producer’s Share (83.49%), sales to Retailers is profitable. However, for commercial scale production role of wholesalers (only 18% of total sales volume) is found to be of utmost importance. The major problem in marketing sweet oranges is the lack of transportation and storage, which also contributes to higher level of local sales. It should be improved before promoting this enterprise and increasing acreage. Development of appropriate infrastructures for facilitating sweet orange marketing is the most for improving the performance of this sub-sector. Cooperative marketing could also be another quick alternative to bring about desirable changes.